Multiple QTL-effects of wheat Gpc-B1 locus on grain protein and micronutrient concentrations. - Distelfeld, A.; Cakmak, I.; Peleg, Z.; Ozturk, L.; Yazici, A. M.; Budak, H.; Saranga, Y.; Fahima, T. (Wiley, 2007)
Micronutrient malnutrition afflicts over three billion people worldwide and the numbers are continuously increasing. Developing genetically micronutrient‐enriched cereals, which are the predominant source of human dietary, is essential to alleviate malnutrition worldwide. Wheat chromosome 6B derived from wild emmer wheat [Triticum turgidum ssp. dicoccoides (Körn.) Thell] was previously reported to be associated with high Zn concentration in the grain. In the present study, recombinant chromosome substitution lines (RSLs), previously constructed for genetic and physical maps of Gpc‐B1 (a 250‐kb locus affecting grain protein concentration), were used to identify the effects of the Gpc‐B1 locus on grain micronutrient concentrations. RSLs carrying the Gpc‐B1 allele of T. dicoccoides accumulated on average 12% higher concentration of Zn, 18% higher concentration of Fe, 29% higher concentration of Mn and 38% higher concentration of protein in the grain as compared with RSLs carrying the allele from cultivated wheat (Triticum durum). Furthermore, the high grain Zn, Fe and Mn concentrations were consistently expressed in five different environments with an absence of genotype by environment interaction. The results obtained in the present study also confirmed the previously reported effect of the wild‐type allele of Gpc‐B1 on earlier senescence of flag leaves. We suggest that the Gpc‐B1 locus is involved in more efficient remobilization of protein, zinc, iron and manganese from leaves to the grains, in addition to its effect on earlier senescence of the green tissues.